The dynamic distribution of the rectal microbiota in Holstein dairy calves provides a framework for understanding early-life gut health - Qi Huang; Fengtao Ma; Yuhang Jin; Duo Gao; Meinan Chang; Peng Sun (Animal Nutrition)
The posterior intestinal microbiota plays a vital role in the growth and health of Holstein dairy calves. However, its establishment and dynamic changes during early development remain unclear. The aim of this study was to investigate microbial colonization and development in the rectum of calves within the first 70 d after birth. Here, 96 rectal content samples were collected from 8 Holstein dairy calves at 12 time points and analyzed using 16S rRNA gene sequencing. The microbial alpha diversity increased with age. The bacterial community displayed a distinct dynamic distribution. The phylum Proteobacteria was replaced by Firmicutes and Bacteroidetes after d 3. The colonization process of bacterial genera in the rectum of neonatal calves can be divided into 2 periods: the colonization period (stage 1: d 1 and stage 2: d 3) and the stable period (stage 3: d 7–14, stage 4: d 21–42, and stage 5: d 49–70). The fermentation pattern and metabolic function changed from propionate fermentation dominated by Shigella to lactic acid fermentation dominated by Lactobacillus, Blautia, and Oscillospira. The stable period was more comprehensive and complete than the colonization period. This study revealed the dynamic changes in the posterior intestinal microbiota of Holstein dairy calves during early development. The transition period (d 7–14) was identified as a key stage for early nutritional intervention, as the abundance of Lactobacillus increased and the abundance of harmful bacteria (such as Proteobacteria and Shigella) decreased. This study provides a framework for understanding early-life gut health and offers theoretical guidance for future research on host–microbe interactions and early nutritional interventions. It is suggested that nutritional interventions based on microbial characteristics at different stages be implemented to improve calf growth performance and immune function, which may contribute to the reduction of diarrhea and other gastrointestinal disorders during dairy production.